Screening of lectins from South American plants used as affinity ligands to purify rhEPO - G.I. Amadeo (Brazilian Journal of Chemical Engineering, 2003)
Two groups of isoforms of rhEPO, at a concentration of 300 µg/ml, were tested as putative inhibitors of the lectinic hemagglutination reaction in order to obtain affinity ligand(s) for hormone purification: groups I (pI: 3.80; 3.89; 3.95; 4.07, 4.15 and 4.26) and groups II (pI: 4.15, 4.26; 4.38; 4.51; 4.72 and 4.93) Crude extracts from the vegetable materials Abrus precatorious (Abrin), Artocarpus incisa (Frutalin), Artocarpus integrifolia (Jacalin), Canavalia ensiformes (ConA), Canavalia brasiliensis (Conbr), Cratylia floribunda, Dioclea altissima (DAL), Dioclea grandiflora (DGL), Erythrina vellutina (EVL), Erythrina cristagalli, Lutaelburgia auriculata (lectin not fully characterized yet), Lycopersicum esculentum (LEA), Phaseolus vulgaris (PHA), Ricinus communis (Ricin) and Triticum vulgaris (WGA) were used. Only some of the galactose-specific lectins and the GlcNAc-specific lectins showed rapid full inhibition of the hemagglutination reaction for the less acidic isoforms and the total isoforms of rhEPO, respectively. On this basis, the selected lectins were purified by affinity chromatoghraphy and covalently coupled to cyanogen bromide activated Sepharose® (Amersham-Pharmacia). CHO.K1 cell culture supernatant containing rhEPO was loaded onto the lectin resins and the recoveries were calculated by using specific elutions.